2010
DOI: 10.1007/s11109-010-9114-0
|View full text |Cite
|
Sign up to set email alerts
|

Affect, Social Pressure and Prosocial Motivation: Field Experimental Evidence of the Mobilizing Effects of Pride, Shame and Publicizing Voting Behavior

Abstract: Citizens generally try to cooperate with social norms, especially when norm compliance is monitored and publicly disclosed. A recent field experimental study demonstrates that civic appeals that tap into social pressure motivate electoral participation appreciably (Gerber et al., Am Polit Sci Rev 102:33-48, 2008).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
139
2
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(153 citation statements)
references
References 36 publications
6
139
2
6
Order By: Relevance
“…7 Panagopoulos (2010) finds that this type of treatment has a positive but weaker effect on voting than listing only those individuals who do not do the socially valued thing. By using this form of the treatment, I am thus both explicitly looking at the effect of promising social esteem (rather than disesteem) and also creating a tougher test for the ingroup status hypothesis.…”
Section: Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…7 Panagopoulos (2010) finds that this type of treatment has a positive but weaker effect on voting than listing only those individuals who do not do the socially valued thing. By using this form of the treatment, I am thus both explicitly looking at the effect of promising social esteem (rather than disesteem) and also creating a tougher test for the ingroup status hypothesis.…”
Section: Treatmentsmentioning
confidence: 99%
“…Individuals may be told that joining in will win them the esteem of other group members. On the flip side of the same coin, they may fear the social shaming that will result if they abstain (Panagopoulos 2010). This third mechanism is rooted in a concern for within-group status.…”
Section: Ingroup Esteem and Rallymentioning
confidence: 99%
See 2 more Smart Citations
“…Soetevent (2005) observed that under specific conditions, church donations increase when neighbors can see how much a person is donating. Panagopoulos (2010) carried out an experiment in which the names of either voters (pride treatment) or nonvoters (shame treatment) in public elections were published in local newspapers and found evidence that shame increased election turn-outs, whereas pride was effective only for sub-groups of society.…”
Section: Hypothesis and Theoretical Predictionsmentioning
confidence: 99%